Pengaruh Gerakan Tanah Terhadap Perencanaan Pembangunan Perumahan (Studi Kasus Perumahan Bukit Regency Semarang) - Subastaryo, Subastaryo (Semarang State University, 2006)
Abstract: People escape from landslide because it brings disadvantage to their materials and soul. Even, Ã‚Â it can bringÃ‚Â calamity. Ã‚Â Landslide Ã‚Â is Ã‚Â very influence Ã‚Â toward construction planning Ã‚Â in Ã‚Â housing, esp. on Bukit Regency Housing in Semarang, Ã‚Â Indonesia. Ã‚Â The Influence of landslide to construction planning Ã‚Â in housing known from stripe faults, Ã‚Â clay stone, spring, Ã‚Â and slope. Ã‚Â Stripe faults can be use for open space, not building. Clay stone, as a landslide layer, consequently followed with foundation treatment, Ã‚Â its Ã‚Â base must be place on compacted breccia Ã‚Â under the clay. Ã‚Â Spring, Ã‚Â as a secondary signal of stripe fault, must be support Ã‚Â with drainage system. Ã‚Â Steep slope, Ã‚Â as landslide plane, Ã‚Â must be change to